Endurance-dependent urinary extracellular vesicle signature: shape, metabolic miRNAs, and purine content distinguish triathletes from inactive people - Tiziana Pietrangelo; Carmen Santangelo; Danilo Bondi; Paolo Cocci; Raffaela Piccinelli; Francesco Piacenza; Enrica Rosato; S. N. Afifa Azman; Enrico Binetti; Marco Farina; Marcello Locatelli; Virgilio Brunetti; et al. (Pflügers Archiv - European Journal of Physiology, 2023)
Extracellular vesicles (EVs) enriched with bioactive molecules have gained considerable attention in nanotechnology because they are critical to intercellular communication while maintaining low immunological impact. Among biological matrices, urine has emerged as a noninvasive source of extracellular-contained liquid biopsy, currently of interest as a readout for physiological adaptations. Therefore, we aimed to evaluate chronic adaptations of endurance sport practice in terms of urinary EV parameters and evaluated by food consumption assessment. Two balanced groups of 13 inactive controls vs. triathlon athletes were enrolled; their urinary EVs were obtained by differential ultracentrifugation and analyzed by dynamic light scattering and transmission electron and atomic force microscopy. The cargo was analyzed by means of purine and miRNA content through HPLC-UV and qRT-PCR. Specific urinary EV signatures differentiated inactive versus endurance-trained in terms of peculiar shape. Particularly, a spheroid shape, smaller size, and lower roughness characterize EVs from triathletes. Metabolic and regulatory miRNAs often associated with skeletal muscle (i.e., miR378a-5p, miR27a-3p, miR133a, and miR206) also accounted for a differential signature. These miRNAs and guanosine in urinary EVs can be used as a readout for metabolic status along with the shape and roughness of EVs, novel informative parameters that are rarely considered. The network models allow scholars to entangle nutritional and exercise factors related to EVs’ miRNA and purine content to depict metabolic signatures. All in all, multiplex biophysical and molecular analyses of urinary EVs may serve as promising prospects for research in exercise physiology.

Genetic structure analysis and selection of a core collection for carob tree germplasm conservation and management - M. Di Guardo; F. Scollo; A. Ninot; M. Rovira; J. F. Hermoso; G. Distefano; S. La Malfa; I. Batlle (Tree Genetics & Genomes, 2019)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

MeMoVolc report on classification and dynamics of volcanic explosive eruptions - C. Bonadonna; R. Cioni; A. Costa; T. Druitt; J. Phillips; L. Pioli; D. Andronico; A. Harris; S. Scollo; O. Bachmann; G. Bagheri; S. Biass; et al. (Bulletin of Volcanology, 2016)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Abundance, Richness, Seasonal and Altitudinal Dynamics of Aquatic True Bugs (Heteroptera) in Mountain Wetlands of Argentina - E. E. Scheibler; M. C. Melo; S. I. Montemayor; A. M. Scollo (Wetlands, 2016)

Characterization of shape and terminal velocity of tephra particles erupted during the 2002 eruption of Etna volcano, Italy - M. Coltelli; L. Miraglia; S. Scollo (Bulletin of Volcanology, 2008)